2012
DOI: 10.1111/j.1532-950x.2012.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle Screw‐Rod Fixation of the Canine Lumbosacral Junction

Abstract: PSRF of the LSJ of large breed dogs is technically possible. Improvements to the surgical technique to induce spinal fusion and assessment in a larger sample size are required before it can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
92
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(101 citation statements)
references
References 56 publications
(178 reference statements)
5
92
0
4
Order By: Relevance
“…With proper training and thorough knowledge of the regional anatomy, these implants can be applied consistently and easily in horses for cervical stabilization. Presently, pedicle screw and rod systems are used routinely in human spinal surgery and are recently having a resurgence of use in veterinary medicine . The polyaxial screw head feature was essential for cervical stabilization in the horse when this technique was used because of the variable shape of the ventral aspect of the cervical vertebral bodies.…”
Section: Discussionmentioning
confidence: 99%
“…With proper training and thorough knowledge of the regional anatomy, these implants can be applied consistently and easily in horses for cervical stabilization. Presently, pedicle screw and rod systems are used routinely in human spinal surgery and are recently having a resurgence of use in veterinary medicine . The polyaxial screw head feature was essential for cervical stabilization in the horse when this technique was used because of the variable shape of the ventral aspect of the cervical vertebral bodies.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the PSRFS is to improve deformity and stabilize the spine in its natural position until fusion has occurred and prevent further degenerative changes [7,9] . In veterinary literatures, PSRFS has been only used to stabilize lumbosacral region after laminectomy for treatment of degenerative lumbosacral stenosis in dogs [10,11,14,15] . Furthermore, the system was used to investigate fusion in lumbar vertebrae [16] .…”
Section: Discussionmentioning
confidence: 99%
“…This is the main problem for safe screw insertions and prediction of the screw dimensions [17] . Smolders et all indicated that CTand/or MRI-based evaluation of the vertebral dimensions of both L7 and S1 is necessary for optimal screw insertion corridors for individual dogs [15] . Before the surgery CT images had been evaluated for pedicle dimensions to predict the dimension of screws dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…No caso relatado, os parafusos foram aplicados exclusivamente nos pedículos vertebrais, no entanto poderia ter sido feita a aplicação dos parafusos envolvendo especificamente os pedículos e os corpos vertebrais de L7 e do sacro, o que possivelmente confere maior rigidez e resistência ao sistema, conforme relataram Meij et al (2007), quando utilizaram parafusos pediculares na coluna lombossacra. Segundo Smolders et al (2012), uma fixação lombossacra em corredores seguros deve ser realizada dorsocaudolateralmente para ventrocraniomedialmente, ou seja, proveniente da cortical dorsal da lâmina até a cortical dorsal do corpo vertebral, sem perfurar a porção cortical ventral assim como as paredes medial e lateral do pedículo. Além disso, sugere-se a perfuração de 20-50% de todo o comprimento do parafuso (Smolders et al, 2012).…”
Section: Discussionunclassified
“…Segundo Smolders et al (2012), uma fixação lombossacra em corredores seguros deve ser realizada dorsocaudolateralmente para ventrocraniomedialmente, ou seja, proveniente da cortical dorsal da lâmina até a cortical dorsal do corpo vertebral, sem perfurar a porção cortical ventral assim como as paredes medial e lateral do pedículo. Além disso, sugere-se a perfuração de 20-50% de todo o comprimento do parafuso (Smolders et al, 2012).…”
Section: Discussionunclassified